An analysis of assessment internal control system in Financial statements audit : the case of aasc - Tran, Thi Hai Yen (2020)
The research topic is directly related to the study audit practices of any audit firm since the assessment of internal control system is a vital part of a financial statements audit. This paper has been written to serve the purpose of providing deeper understanding analyzed into the topic as well as a realistic glimpse into audit practices of a professional audit company. Three main reason for the necessity of conducting evaluation of internal control system are as follow: The first reason comes from VSA’s requirement for auditor to evaluate the risk of material misstatement by assessing internal control system in any financial statement audit.